Genome-wide identification and expression analysis of glycogen synthase kinase encoding genes in foxtail millet (Setaria italica L.) under salinity, dehydration, and oxidative stress - Jawahar Singh; Vishal Varshney; Nisha Tak; Shweta Jha (Plant Stress, 2023)
Glycogen Synthase Kinase 3 (GSK3)/SHAGGY-like Kinase (SK) proteins in plants govern growth, development, and several abiotic and biotic stress responses. GSK3 proteins are cytoplasmic serine/threonine kinases that control glycogen metabolism in eukaryotes. However, nothing is known about the discovery and characterization of glycogen synthase kinase (GSK) genes in foxtail millet (Setaria italica). In the present study, eight Setaria italica GSK (SiGSKs) genes were identified and divided into four groups based on their phylogenetic affinities with rice and Arabidopsis. The gene structure and motif organizations were examined to delve deeper into SiGSKs function and its evolution. The SiGSKs encode active protein kinases, according to conserved motif and kinase domain analysis. Many growth hormones and stress-responsive elements were found in the SiGSK promoter regions, which is compatible with their expression in diverse organs and their changed expression in response to abiotic stress such as salt, drought, and oxidative damage. qRT-PCR expression analysis of SiGSKs under three different abiotic stresses suggests its role in signaling and regulating the mechanism under the mentioned abiotic stresses. The current research opens up new opportunities for SiGSK functional validation in S. italica (L.) by genetic engineering.